Developing a standard approach for assessing the hydromorphology of lakes in Europe. Issue 4 (9th January 2019) - Boon, Philip; Argillier, Christine; Boggero, Angela; Ciampittiello, Marzia; England, Judy; Peterlin, Monika; Radulović, Snežana; Rowan, John; Soszka, Hanna; Urbanič, Gorazd
Abstract: Methods for assessing the hydrology and morphology of lakes ('hydromorphology') are needed for reporting under national and international legislation, as well as to assist in lake management and restoration. Despite this, no consistent approaches have been developed around Europe for monitoring lake hydromorphology. To address this need, representatives from 12 countries met at a series of workshops to develop two protocols for monitoring, published under the auspices of the European Committee for Standardization (CEN). The first standard (EN 16039) describes six categories for assessing lake hydromorphology: hydraulics, morphometry, bedforms/landforms and substrate, connectivity and continuity, and land cover. The second standard (EN 16870) sets out a scoring system for assessing the degree of modification of lake hydromorphology, which was designed, tested and refined using data from 127 lakes in seven European countries. The CEN standards focus on four lake zones—riparian, shore, littoral, and open water—but recognize the importance of considering lakes within their wider catchment context. The field techniques described are based largely on Lake Habitat Survey but also rely on existing databases, maps and remote‐sensing data. These standards are aimed at scientists, conservation bodies and environmental regulators, and are relevant not only for monitoring lakes under the Water Framework Directive, but also for contributing to programmes of lake conservation. For example, in the UK, parts of the CEN standards have been incorporated within the methods used for monitoring and reporting on the condition of Special Areas of Conservation (under the Habitats Directive) and Sites of Special Scientific Interest under national legislation. It is hoped that this pan‐European approach will improve the ability to compare data across many countries, and ultimately ensure that the results of monitoring are translated into measures for improving the hydromorphological condition of lakes and the biological communities they contain.